2006
DOI: 10.1254/jphs.dtj05001x
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological, Pharmacokinetic, and Clinical Properties of Benidipine Hydrochloride, a Novel, Long-Acting Calcium Channel Blocker

Abstract: Abstract. Benidipine is a dihydropyridine-derived calcium channel blocker developed in Japan, with several unique mechanisms of action, that is, triple calcium channels (L, N, and T) blocking action with a membrane approach. Benidipine has relatively high vascular selectivity and is expected to show protective effects on vascular endothelial cells. Renal protective effects of benidipine also have been shown in several basic and clinical studies. Moreover, anti-oxidative action and enhancing nitric oxide produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
69
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 86 publications
(79 reference statements)
2
69
0
1
Order By: Relevance
“…The partition coefficient of benidipine has been reported to be 3.79 using the flask-shaking method. 36) In accordance with the product interview forms, the partition coefficient of PGF2α analogs are 4.3 for latanoprost, 4.5-4.6 for tafluprost, and 3< for travoprost (no description for bimatoprost). Moreover, they are partially distributed through the nasopharyngeal mucosa to the whole body without being metabolized by the hepatic enzyme, indicating the very high liposolubility.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…The partition coefficient of benidipine has been reported to be 3.79 using the flask-shaking method. 36) In accordance with the product interview forms, the partition coefficient of PGF2α analogs are 4.3 for latanoprost, 4.5-4.6 for tafluprost, and 3< for travoprost (no description for bimatoprost). Moreover, they are partially distributed through the nasopharyngeal mucosa to the whole body without being metabolized by the hepatic enzyme, indicating the very high liposolubility.…”
Section: Discussionmentioning
confidence: 78%
“…This concept can clearly explain its strong and long-lasting activity and could apply to PGF2α analogs. It is said that this property seems to be associated with its high affinity for cell membranes, 36) and the water-to-octanol partition coefficient (log P ow ) is available as an index. The partition coefficient of benidipine has been reported to be 3.79 using the flask-shaking method.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Benidipine is a potent and long-acting dihydropyridine calciumchannel blocker (CCB), which inhibits not only L-type and N-type calcium channels but also T-type calcium channels, and regulates the constriction and dilation of renal efferent arterioles. 5 The Combination Therapy of Hypertension to Prevent Cardiovascular Events (COPE) trial is a prospective, randomized, open-label, blinded-endpoint (PROBE) study to determine the optimal combination of CCB benidipine-based therapy for hypertension, 6,7 and the main results have demonstrated that the percentage of subjects achieving the target BP and the incidence of primary composite cardiovascular end points were similar among benidipine-thiazide diuretic (thiazide), benidipine-angiotensin-receptor blocker (ARB) and benidipine-b-blocker subgroups. However, second analyses suggested that benidipine combined with a b-blocker appeared to be less beneficial in reducing the risk of stroke compared with the benidipine-thiazide combination, and was associated with an increased incidence of new-onset diabetes compared with the benidipine-ARB combination.…”
Section: Introductionmentioning
confidence: 99%
“…Mibefradil selectively blocks T-type calcium channels and has been demonstrated to exert a cardioprotective effect in rats with acute myocardial infarction (28). Benidipine has been widely used for hypertension therapy as it is able to block the L-type and T-type calcium channels in various cell types (29).…”
Section: Discussionmentioning
confidence: 99%